IMPLIKASI DALIL QATH'I DAN ZHANNI DALAM PENERAPAN HUKUM - Abbas, Salmi (MEDIA HUKUM, 2014)
Islam is a religion of revelation bestowed by the God to His Prophets and His deciples, since from Adam Alahissalam and following to the Mohammed Prophet , as the last Prophet to the end of the world. Islam has been brought by Mohammed prophet , that become the completion of religions before. The Islamic congregations in Rasululah Saw's tims and His friends, in applying the rules from Alqur'an and Hadist Rasululah never got difficulties, because besides the language factor from Alqur'an and Hadist (by their own mother tounges), they also asked Rasulullah directly if they did not understant the nats. So as to the passing time, and the Islam has spreaded over the world, and of course it is already far away from the own sources , so to apply the Islamic Law to approach to its origines, it is needed the norms that are coming from the souls and the Islamic Spirit of Law itsself.